2018
DOI: 10.1021/acs.jnatprod.7b00927
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrodiconiferyl Alcohol Inhibits Osteoclast Differentiation and Ovariectomy-Induced Bone Loss through Acting as an Estrogen Receptor Agonist

Abstract: Estrogen deficiency after menopause increases bone loss by activating RANKL-induced osteoclast differentiation. Dehydrodiconiferyl alcohol (DHCA), a lignan originally isolated from Cucurbita moschata, has been thought to be a phytoestrogen based on its structure. In this study, we tested whether DHCA could affect RANKL-induced osteoclastogenesis in vitro and ovariectomy-induced bone loss in vivo. In RAW264.7 cells, DHCA inhibited RANKL-induced differentiation of osteoclasts. Consistently, expression of the six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…MAPK is in the serine‐threonine protein kinase family that is involved in cell viability, differentiation, apoptosis, inflammation and innate immunity . The most studied proteins of the MAPK pathway are ERK, JNK and p38 kinases, which can respond to extracellular stimuli including growth factors, heat shock proteins and pro‐inflammatory cytokines . Specific inhibitors of JNK, p38 and ERK can inhibit RANKL‐stimulated osteoclast differentiation, indicating that MAPK is important for osteoclast activation and bone resorption .…”
Section: Discussionmentioning
confidence: 99%
“…MAPK is in the serine‐threonine protein kinase family that is involved in cell viability, differentiation, apoptosis, inflammation and innate immunity . The most studied proteins of the MAPK pathway are ERK, JNK and p38 kinases, which can respond to extracellular stimuli including growth factors, heat shock proteins and pro‐inflammatory cytokines . Specific inhibitors of JNK, p38 and ERK can inhibit RANKL‐stimulated osteoclast differentiation, indicating that MAPK is important for osteoclast activation and bone resorption .…”
Section: Discussionmentioning
confidence: 99%
“…After menopause, estrogen deficiency leads to the higher levels of RANKL and proinflammatory factors, including IL-6 and TNF-a (Sun et al, 2018). The over-activation of RANKL signaling pathways recruits the RANK/TRAF6 association and thus promotes the reproduction of osteoclasts Lee et al, 2018). As a result, it is a potential therapeutic target for PMOP via inhibiting osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it was found to exert anti- Helicobacter pylori [ 59 ], antiadipogenic [ 60 ], and antioxidant effects [ 61 ]. Recently, Lee et al reported that (-)-dehydrodiconiferyl alcohol suppresses the p38 MAPK and NF-κB signaling pathways in RAW 264.7 cells and acts as an estrogen receptor agonist [ 62 ]. Moreover, it exerts anti-inflammatory activity by regulating key molecules involved in inflammation and oxidative stress, such as pro-inflammatory cytokines (TNF-α, IL-6 and IL-1β) and mediators (iNOS, COX-2, and ROS) [ 63 ].…”
Section: Discussionmentioning
confidence: 99%